Description of the Prevalence of Hypertension in Ambon Port Health Office: (Case Study of Clinical Data in Ambon KKP Work Area in 2016) - Ruddy La Unga; Mateus Sakundarno (Universitas STRADA Indonesia, 2019)
Hypertension is one of the risk factors that play a role in the occurrence of cardiovascular disease. At Ambon Port Health Office the prevalence is 35.8%. Although prevalence is known but the prevalence distribution according to people, place and time is unknown. So the purpose of this study was to describe the prevalence and distribution of hypertension events according to people, place and time in the work area of ​​the Ambon Port Health Office. This type of research is descriptive observational research with case study research design.